2019
DOI: 10.1161/jaha.118.010905
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Consent: Patients’ and Surrogates’ Perspectives on Consent for Clinical Trials in Acute Stroke and Myocardial Infarction

Abstract: Background Emergent informed consent for clinical trials in acute myocardial infarction (AMI) and stroke is challenging. The role and value of consent are controversial, and insufficient data exist regarding patients’ and surrogates’ experiences. Methods and Results We conducted structured interviews with patients (or surrogates) enrolled in AMI or acute stroke trials at 6 sites between 2011 and 2016. Primary domains included trial recall, consent experiences, and prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Accordingly, they expressed support for discussions about organ donor intervention research while on the waitlist. 29 Finally, research on organ donors (rather than directly on organs) raises the issue of risks to bystander organs that were not the intended target of the intervention. These patients' preferences validate the National Academy of Science committee's recommendations that transplant programs inform candidates about intervention organs at multiple times (eg, at waitlisting, and at the organ offer).…”
Section: Study Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, they expressed support for discussions about organ donor intervention research while on the waitlist. 29 Finally, research on organ donors (rather than directly on organs) raises the issue of risks to bystander organs that were not the intended target of the intervention. These patients' preferences validate the National Academy of Science committee's recommendations that transplant programs inform candidates about intervention organs at multiple times (eg, at waitlisting, and at the organ offer).…”
Section: Study Conclusionmentioning
confidence: 99%
“…28 Approaches to consent outside transplantation show that there are promising avenues for respecting these values, while minimizing some burdensome features (eg, a long paper form; extensive time for discussion, as needed) typical of research in other clinical settings. 29 Finally, research on organ donors (rather than directly on organs) raises the issue of risks to bystander organs that were not the intended target of the intervention. Most participants preferred providing informed consent to accept a bystander organ given the potential for additional risks.…”
Section: Study Conclusionmentioning
confidence: 99%
“…Informed consent is a mechanism for patients to exercise autonomy in trial enrollment, but patients and their surrogates also derive value from informed consent discussions. (35,36) As such, the manner of patient participation is intrinsically an ethical factor in trials without straightforward informed consent processes, such as trials of acute stroke or other emergency treatments. Investigators surveyed from the AbESTT II trial indicated that obtaining informed consent produces unnecessary delays, but simultaneously felt an exemption for informed consent was inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Phone consent is important when no proxy is available within the time window due to geographic constraints. (36,50) However, it can be challenging to reach patient families with distressing information and ask for a decision when they are most vulnerable. Another solution to consider in the case of acute stroke trials may be a waiver of consent, known as an exception from informed consent (EFIC) in the USA, as delays in treatment due to the time it takes to achieve informed consent can lead to worse outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation